ANALYSIS OF LEXICAL AND CONTEXTUAL MEANING IN RAEF’S SONG LYRIC OF THE PATH ALBUM AS THE HOLY QUR’AN VALUES - Hasanah, Risalatul; Habibullah, Mosleh (PANYONARA: Journal of English Education, 2020)
The Holy Qur?an is guidance to live, some of its meaning can be inserted into the lyric of the song, such as Raef?s song lyrics. Three research focuses are proposed, i.e how are the lexical meaning, how are the contextual meanings, and what are the Holy Qur?an values consists of Raef?s song lyric in The Path album. This study is a library. The data sources are Raef?s song lyric of The Path album which consists of 12 lyrics of songs, and the Holy Qur'an values. The finding revealed that in the lexical analysis, the meaning of a word is varied, for example, the keyword of "words" in Peace and Blessing lexically means languages, utterances, promises, signals, and teachings. And contextually, the intended meaning of it is sunnah, then from those meanings, it will relate to the Holy Qur'an value which supports the lyric of song, namely an-Nur (24): 54 which contains the value of Sunnah and the obligation to follow sunnah of Rasulullah, and it relates to the lyric of song when it also talks about the same thing. That kind of findings is also similar to the other analysis in all Raef?s song lyrics of The Path album